Molecular characteristic of three threatened Hopea species in Vietnam - Phuong Trang, Nguyen Thi; Huong, Tran Thu; Triest, Ludwig; Tam, Nguyen Minh (Academia Journal of Biology, 2015)
Hopea chinensis Hand-Mazz, Hopea hainanensis Merr. & Chun and Hopea mollissima C.Y.Wu are high value timber species and have high value in science and medicine. Currently, these three species are over exploited and are listed in the Red book. Typicaly, Hopea hongayensis and H.  mollissima shared many very similar morphology characteristics and often confusion. To provide molecular database for taxonomy and raising the effect of conservation to sustainable development of these species in Vietnam, three chloroplast gene regions including rbcL, matK, psbA-trnH of these three Hopea species were sequenced. The results showed that there are 6 different nucleotide positions were found between Hopea hongayensis Tardieu and Hopea mollissima C.Y.Wu. According that, the genetic distance between H chinensis and H. mollissima is 2%.  Seven different nucleotide positions were found between H. chinensis and H. hainanensis, the genetic distance between H. hainanensis with H. chinensis and H. mollissima is 4% and 6%, repectively.